2017
DOI: 10.1097/pr9.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

Preventing and treating medication overuse headache

Abstract: Medication overuse headache is a secondary headache—a worsening of a pre-existing headache (usually a primary headache) owing to overuse of one or more attack-aborting or pain-relieving medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
0
24
0
2
Order By: Relevance
“…Medication overuse headache, linked to overuse of attack aborting medication, is an important consideration with patients presenting to the specialist headache clinic. Its prevalence in the general adult population of different countries ranges from 0.5% to 7.6% . In patients with chronic daily headache, its prevalence may be as high as 11‐70% .…”
Section: Epidemiologymentioning
confidence: 99%
“…Medication overuse headache, linked to overuse of attack aborting medication, is an important consideration with patients presenting to the specialist headache clinic. Its prevalence in the general adult population of different countries ranges from 0.5% to 7.6% . In patients with chronic daily headache, its prevalence may be as high as 11‐70% .…”
Section: Epidemiologymentioning
confidence: 99%
“…Analgesic consumption must be carefully evaluated. Frequent use of all types of pain-relieving drugs, in particular triptans, ergotamine, opioids, caffeine, meprobamate and codeine-containing products, may be associated with rebound headache, which itself is associated with greater pain-related disability 53,54. Withdrawal of treatment often leads to improvement and evolution to episodic headache.…”
Section: Practical Approach To Pain Management In Chronic Pain Of Uncmentioning
confidence: 99%
“…Opioids are included in this rationale to be consistent with the International Classification of Headache Disorders regarding medication overuse). It has been suggested that clinicians consider preventive treatments in these populations . Although there are no data on this topic in pediatric populations, it is hypothesized that similar relationships between frequent headache, medication overuse, and progression to chronic migraine may occur in children.…”
Section: Practice Recommendationsmentioning
confidence: 99%